2019
DOI: 10.1002/mp.13549
|View full text |Cite
|
Sign up to set email alerts
|

Impact of noise reduction schemes on quantitative accuracy of CT numbers

Abstract: Purpose: In previous works, it has been demonstrated that for filtered backprojection (FBP) reconstruction-based computed tomography (CT) images, the measured CT numbers are biased and the bias level decreases with increasing radiation dose. Low-dose scans typically include noise reduction schemes to reduce noise level. The purpose of this work was to investigate the potential impact of different noise reduction schemes on the CT number bias. Methods: Three different filtration methods: Gaussian, adaptive trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Due to radiation safety and other practical considerations, the estimation of sinogram data for CT reconstruction has been using N instead of N. As reviewed in Section 2.1, the use of stochastic N leads to statistical bias and noise. The statistical bias becomes more severe with lower radiation exposure and smaller detector pixels, such as those used in low-dose highresolution PCD-CT. Statistical bias has been observed in both EID-CT and PCD-CT, and previous works have proposed methods to mitigate it using data filtration 29 or iterative reconstruction techniques. 30 The effectiveness of these methods is dependent on the parameter selection and often has a tradeoff with spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to radiation safety and other practical considerations, the estimation of sinogram data for CT reconstruction has been using N instead of N. As reviewed in Section 2.1, the use of stochastic N leads to statistical bias and noise. The statistical bias becomes more severe with lower radiation exposure and smaller detector pixels, such as those used in low-dose highresolution PCD-CT. Statistical bias has been observed in both EID-CT and PCD-CT, and previous works have proposed methods to mitigate it using data filtration 29 or iterative reconstruction techniques. 30 The effectiveness of these methods is dependent on the parameter selection and often has a tradeoff with spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical bias has been observed in both EID‐CT and PCD‐CT, and previous works have proposed methods to mitigate it using data filtration 29 or iterative reconstruction techniques 30 . The effectiveness of these methods is dependent on the parameter selection and often has a tradeoff with spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…A recent phantom study by [30] also reported that a deviation of 4.3 HU was obtained from a misalignment of 80 mm with a low-tube voltage. This can result in inaccurate diagnosis [31]. In some circumstances, the misalignment can increase the patient dose, causing an unnecessary dose received by patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, misalignment up to 10 mm does not cause significant artifacts to appear. Several studies have reported that misalignment can cause changes in image noise and dose at certain position within the phantoms or patients [29][30][31][32][33]. Further studies are needed on the influence of misalignment on the emergence of artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the networks often result the distortion in pixel values. Unfortunately, the change of the CT numbers has detrimental effects to the radiological diagnostic performance, since it is used as a diagnostic indicator [6]. Especially in the temporal bone CT scans which we are interested in this paper, the CT number supports the evaluation of a pathologies of the ear, such as an inflammation within the inner ear, and a cholesteatoma in early stage [5,13,1].…”
Section: Introductionmentioning
confidence: 99%